(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This research explored how secondary school teachers' motivation, involvement in Learning Action Cell activities, and instructional effectiveness are related. Using a quantitative, descriptive-correlational approach, the study surveyed Valencia National High School-licensed teachers in the 2025–2026 academic year. Extrinsic, social, and professional development, and intrinsic motivation were consistently high, with intrinsic motivation cited as the most important component of successful training. Teachers regularly participated in Learning Action Cell activities, including professional development, group planning, and monitoring, which enhanced instruction delivery, as evidenced by student engagement, feedback, topic mastery, and evidence-based practices. Regression analysis demonstrated that social motivation, reflective practice, professional development, and intrinsic motivation were all significant predictors of teaching effectiveness, and that there were significant positive relationships between motivation, collaborative practice, and instructional delivery. The results emphasised the importance of promoting professional cooperation and personal fulfilment to improve teaching effectiveness.